A fast method for modelling skew and its effects in salient-pole synchronous generators - Nuzzo, Stefano; Galea, Michael; Gerada, C.; Brown, Neil (Institute of Electrical and Electronics Engineers, 2017)
The general effects of implementing skewing techniques in electrical machines are well known and have been extensively studied over the years. An important aspect of such techniques is related to the identification of optimal methods for analyzing and modelling any skewed components. This paper presents a fast, finite-element-based method, able to accurately analyze the effects of skew on wound-field, salient-pole synchronous generators in a relatively shorter time than the more traditional methods. As vessel for studying the proposed technique, a 400kVA alternator is considered. Analytical and theoretical considerations on the benefits of skewing the stator in the generator under analysis are preliminary carried out. A finite-element model of the machine is built and the proposed method is then implemented to investigate the effects of the skewed stator. Comparisons against more traditional techniques are presented, with focus on the analysis of the voltage total harmonic distortion and the damper bars’ currents. Finally, experimental tests are performed at no-load and on-load operations for validation purposes, with excellent results being achieved.